Analyzing the Influence of Concept Understanding and Self Efficacy on Student’s Algebraic Thinking Ability in Flipped Classroom Learning Model - Kurniawan, Muhammad Rizcky; Mashuri, Mashuri (Unnes Journal of Mathematics Education, 2021)
The concept understanding and self efficacy are needed in mathematics learning. One of the student’s skills in mathematics learning is the ability to think. The aims of this study is an analyzing the influence of concept understanding and self-efficacy on students' algebraic thinking abilitys and describe the algebraic thinking ability in the flipped classroom learning model based on concept understanding and self efficacy. This research is included in the mix-method research with sequential explanatory design. The results showed that (1) the average concept understanding and algebraic thinking ability of students who were given the flipped classroom learning model achieved learning completeness; (2) the average concept understanding and algebraic thinking ability of students who were given the flipped classroom learning model were better than those given the direct instruction learning model; (3) there is an influence between concept understanding and self-efficacy on students' algebraic thinking ability both simultaneously and partially; (4) i) students who have high concept understanding and high self efficacy tend to have high algebraic thinking ability; ii) students who have high concept understanding and moderate self efficacy than moderate concept understanding and moderate and low self efficacy tend to have moderate algebraic thinking ability; and iii) students who have low concept understanding and self efficacy tend to have low algebraic thinking ability.